PENGEMBANGAN MEDIA PEMBELAJARAN FIQIH BERBASIS WEB (HTML) UNTUK MEMVISUALISASIKAN TATA CARA SHALAT JENAZAH PADA SISWA TINGKAT SMA/MA - Fajarwati, Anita; Burhanuddin, Hamam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study was to develop and test the feasibility and effectiveness of a web-based (HTML) fiqh learning media to visualize the procedures of funeral prayer for senior high school students (SMA/MA). The method used was Research and Development (R&D) with the ADDIE model through five stages: Analyze, Design, Development, Implementation, and Evaluation. The trial subjects included material experts (2 persons), media experts (2 persons), learning practitioners (1 teacher), as well as students in one-to-one trials (3 students), small group trials (9 students), and field trials (30 students). Data collection instruments included validation questionnaires, student response questionnaires, pre-tests, and post-tests. The results showed that the developed media was highly feasible, with feasibility percentages of 90–95% from material experts, 83–96% from media experts, and 95–97% from learning practitioners. The effectiveness test showed a significant improvement in learning outcomes with an N-Gain score of 0.59 (moderate category) and a t-test value (13.356 > 2.032; p < 0.001). Student responses to the media ranged from 82.3% to 87% in the very good category. In conclusion, this web-based learning media is effective and feasible to enhance students' understanding of the funeral prayer procedures.